Give me eighty men : women and the myth of the Fetterman Fight - Smith, Shannon D., 1958- (Women in the West., 2008)
In Give Me Eighty Men, Shannon D. Smith reexamines the works of the two Mrs. Carringtons in the context of contemporary evidence. No longer seen as an arrogant firebrand, Fetterman emerges as an outstanding officer who respected the Plains Indians' superiority in numbers, weaponry, and battle skills. Give Me Eighty Men both challenges standard interpretations of this American myth and shows the powerful influence of female writers in the nineteenth and twentieth centuries.